Transition from unemployment to employment: monitoring, indicators, comparative analysis - Pocius, Arūnas; Moskvina, Julija; Gruževskis, Boguslavas (Lithuanian Journal of Statistics, 2024)
Indicators that reflect the transition from unemployment to employment are an important element of the monitoring systems of employment services in EU countries. Monitoring employment trends is a complex task that usually goes beyond quantitative parameters. The correct application and interpretation of the indicators is inseparable from contextual phenomena, and the use of comparative analyses at different scales, e.g. time, territory, makes it possible to increase the informativeness of this indicator. The aim of the paper is to identify, on the basis of the available data, the trends in the transition from unemployed to employment at the national and territorial level, and to forecast possible shirt-term development scenarios for the selected jobplacement indicators. The methodological part of the paper assesses the links between unemployment trends and jobplacement indicators. The methodological approach to the assessment of differentiation of jobplacement indices are described there. On the basis of the data from the customer service units of the national Employment Service, an analysis of the spatial distribution of the transition of the registered unemployed to employment was conducted. The forecast of the indicators was based on short-term historical data from the customer service units and economic context variables. In the face of relatively unfavourable forecasts for the EU economic situation, the paper presents the assumptions for changes in the situation on the Lithuanian labour market in the short term.